Facilitating the development of location-based experiences - Oppermann, Leif (2009)
Location-based experiences depend on the availability and reliability of wireless infrastructures such as GPS, Wi-Fi, or mobile phone networks; but these technologies are not universally available everywhere and anytime. Studies of deployed experiences have shown that the characteristics of wireless infrastructures, especially their limited coverage and accuracy, have a major impact on the performance of an experience.